Clinical Response of Levodopa in CTNNB1-Related Dystonia - Revert Barberà, Anna; Martorell, Loreto; Boix, Cristina; Armstrong, Judith; Carrera, Laura; Nascimento, Andrés; Ortigoza-Escobar, Juan Darío (Journal of Pediatric Neurology, 2024)
β-catenin, which is encoded by the CTNNB1 gene, is essential for the development and functioning of the brain. There are a few documented cases of dystonia related to CTNNB1. Here, we report the case of an 11-year-old Spanish boy referred for movement disorders and gait disturbance. He had motor developmental delay and achieved unassisted walking at 3 years, with a tiptoe gait and valgus foot posture requiring ankle-foot orthoses. Blood tests showed elevated creatine kinase levels (1684 U/L, normal range 62–235). Molecular analysis revealed a deletion in exons 3-9 of the DMD gene, leading to the diagnosis of Becker muscular dystrophy. By age 8, he presents frequent falls due to a dystonic posture of the feet and abnormal movements in the upper and lower limbs. Whole-exome sequencing revealed a novel heterozygous, de novo pathogenic frameshift variant in the CTNNB1 gene (NM_001098209.1):p.Thr297fs/ c.889dupA. Treatment with levodopa/carbidopa (5.3 mg/kg/day) led to a partial clinical improvement, including a decrease in dystonia, measured by the Burke-Fahn-Marsden Dystonia Rating Scale, and choreic movements in all four limbs. We suggest that levodopa contributes to motor improvement in patients with CTNNB1-related dystonia, supporting its inclusion in the differential diagnosis of childhood dopa-responsive dystonia.
Keywords: CTNNB1; levodopa; dystonia; intellectual disability; Becker muscular dystrophy